META-ANALISIS PENGARUH PENERAPAN MODEL PEMBELAJARAN INKUIRI DALAM HASIL BELAJAR FISIKA SISWA - Irpan Irpan; Yoga Budi Bhakti (Jambura Physics Journal, 2020)
This research is a meta-analytic study that uses qualitative analysis methods with documentation data collection techniques with pusposive sampling techniques. In 10 journal articles analyzed that the results of 10 research journal articles show that the effect of the application of the inquiry learning model has an effect on the learning process results. The application of this inquiry model has a significant influence on learning achievement such as science process skills, conceptual understanding, creative thinking skills and student learning outcomes. With this inquiry learning model, it has a positive influence on the achievement of students in learning. From the analysis of 10 journal articles, it is clear that the application of learning with this inquiry learning model has a positive influence on student understanding and student learning outcomes in physics learning.